One Orebody ù Two Tenements ù Multiple Owners: How to Apportion Costs and Production Equitably Over the Mine Life? (The Australasian Institute of Mining and Metallurgy, 2002)
Production sharing and cost apportionment in joint ventures is commonplace in Australasia today and elsewhere. It is a recognised convention that, with the exception of a free carry situation, joint venture participants usually share the proceeds of the joint venture in direct proportion to their respective participating interest, after having first paid its respective cash calls, in advance, to cover the projectÆs ongoing operating and capital cost requirements.In surface mines, the parties simply pay their way and take their proceeds in this manner. In underground mines, the situation is no different, though treatment of capital, depreciation and tax may differ between the parties. A common feature in many cases is the creation of a joint venture entity to conduct the business. This entity then collects cash from the parties, banks it, employs the staff, runs the operation, provides reports and pays out the proceeds. This convention appears to be relatively simple in application. In practice, it has been known to be complicated in the situation where the participants take their product at the mine gate and undertake their own marketing and selling arrangements. A more complex situation presents itself where the joint venture tenement boundary with an unrelated third party straddles an economic deposit. In this scenario, both the joint venture parties and the third party may wish to mine the deposit, sharing some infrastructure and costs, yet taking their own product as it is produced. A case study outlining such a situation is presented in the paper, outlining firstly how the major cost categories were identified and treated for cost apportionment purposes. Secondly, a mechanism for the equitable apportionment of product is suggested. Finally, issues such as timing and cost reporting are dealt with, together with a checklist of points which should be considered when a similar situation might arise in the future.